Genetic and biochemical markers of hydroxyurea therapeutic response in sickle cell anemia - Humberto Silva, Danilo Grunig [UNESP]; Belini Junior, Edis [UNESP]; Souza Carrocini, Gisele Cristine de [UNESP]; Torres, Lidiane de Souza [UNESP]; Ricci Junior, Octavio; Castro Lobo, Clarisse Lopes de; Bonini-Domingos, Claudia Regina [UNESP]; Almeida, Eduardo Alves de [UNESP] (Biomed Central Ltd., 2013)
Background: Sickle cell anemia (SCA) presents a complex pathophysiology which can be affected by a number of modifying factors, including genetic and biochemical ones. In Brazil, there have been no studies verifying beta(S)-haplotypes effect on oxidative stress parameters. This study evaluated beta(S)-haplotypes and Hb F levels effects on oxidative stress markers and their relationship with hydroxyurea (HU) treatment in SCA patients.Methods: The studied group was composed by 28 SCA patients. Thirteen of these patients were treated with HU and 15 of them were not. We used molecular methodology (PCR-RFLP) for hemoglobin S genotype confirmation and haplotypes identification. Biochemical parameters were measured using spectrophotometric methods (Thiobarbituric-acid-reactive substances and Trolox equivalent antioxidant capacity levels, catalase and GST activities) and plasma glutathione levels by High-performance liquid chromatography coupled to electrochemical detection.Results: We found the highest frequency of Bantu haplotype (48.2%) which was followed by Benin (32.1%). We observed also the presence of Cameroon haplotype, rare in Brazilian population and 19.7% of atypical haplotypes. The protective Hb F effect was confirmed in SCA patients because these patients showed an increase in Hb F levels that resulted in a 41.3% decrease on the lipid peroxidation levels (r=-0.74, p=0.01). Other biochemical parameters have not shown differential expression according to patient's haplotypes. Bantu haplotype presence was related to the highest lipid peroxidation levels in patients (p<0,01), but it also conferred a differential response to HU treatment, raising Hb F levels in 52.6% (p=0.03) when compared with the group with the same molecular profile without HU usage.Conclusions: SCA patients with Bantu haplotype showed the worst oxidative status. However these patients also demonstrated a better response to the treatment with HU. Such treatment seems to have presented a haplotype-dependent pharmacological effect.
Keywords: Hemoglobin S; Beta-S-gene cluster haplotypes; Oxidative stress; Antioxidant capacity